Functions of Conserved Motifs in the RNA-Dependent RNA Polymerase of a Yeast Double-Stranded RNA Virus - Routhier, Eric (American Society for Microbiology, 1998)
At least eight conserved motifs are visible in the totivirus RNA-dependent RNA polymerase (RDRP). We have systematically altered each of these in the Saccharomyces cerevisiae double-stranded RNA virus ScVL1 by substituting the conserved motifs from a giardiavirus. The results help define the conserved regions of the RDRP involved in polymerase function and those essential for other reasons.